The Role of Inclusive Education as a Container for Equal Education: Analysis of Effectiveness and Problems - Iman, Mujhirul; Syafiq, Zoe Zarka; Farhana, Farhana; Ramadina, Rifda; Nasution, Fina Safitri (LPPPI Publishing, 2024)
Inclusive education is a form of school where children with disabilities have the opportunity to learn together with other normal children. Inclusive education has become a new facility for children with disabilities or children who have extraordinary intelligence to increase their potential without having to be separated from normal society in general. Basically, they are also Indonesian citizens who also have the same opportunity to obtain education. The presence of inclusive education brings a new color to the world of education. One way that can be taken to accommodate inclusive students in understanding the material is through inclusive education. Research with a qualitative approach aims to understand the main focus of the title on the role of inclusive education as a forum for educational equality. The main focus of this research is qualitative so that the author and readers provide a lot of learning and are also able to think carefully regarding the main points in the title and discussion presented. The government has taken various strategies to develop inclusive education. However, it cannot be denied that there are still many problems regarding the role of inclusive education as a means of equalizing education in this country. The lack of role and activity from certain parties creates problematic differences between regular or normal schools compared to schools with special needs. There are many questions and statements that need to be discussed and deliberated on in the context of education in this country. Inclusive education should also be a pillar in developing the quality of a country's education as a forum that continues to be able to develop and guide children in terms of education. Potential children's characters also have a wide variety of creativity and skills, talents that they use as a momentum for their arguments in competition.